2017
DOI: 10.1080/17535069.2016.1275618
|View full text |Cite
|
Sign up to set email alerts
|

The New Urban Agenda: key opportunities and challenges for policy and practice

Abstract: The UN-HABITAT III conference held in Quito in late 2016 enshrined the first Sustainable Development Goal (SDG) with an exclusively urban focus. SDG 11, as it became known, aims to make cities more inclusive, safe, resilient and sustainable through a range of metrics, indicators, and evaluation systems. It also became part of a post-Quito 'New Urban Agenda' that is still taking shape. This paper raises questions around the potential for reductionism in this new agenda, and argues for the reflexive need to be a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
110
0
4

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 261 publications
(126 citation statements)
references
References 28 publications
0
110
0
4
Order By: Relevance
“…An aspect often missing from discussions of global urban agendas is the role of citizens (Caprotti et al 2017;Kaika 2017). Analyses from the implementation of the MDGs have shown that urban poor groups have usually not been involved in the design of interventions meant to assist them, with national or regional consultations involving some civil society groups representing a weak kind of 'participation' (Hasan et al 2005, p. 6).…”
Section: ) Actorsmentioning
confidence: 99%
See 1 more Smart Citation
“…An aspect often missing from discussions of global urban agendas is the role of citizens (Caprotti et al 2017;Kaika 2017). Analyses from the implementation of the MDGs have shown that urban poor groups have usually not been involved in the design of interventions meant to assist them, with national or regional consultations involving some civil society groups representing a weak kind of 'participation' (Hasan et al 2005, p. 6).…”
Section: ) Actorsmentioning
confidence: 99%
“…Potential trade-offs and synergies among efforts to reach different goals relate in part to the boundary discussion above. Such interconnections need to be taken into account by all who strive to implement the SDGs and NUA (Caprotti et al 2017;Machingura and Lally 2017;Nilsson et al 2017). Systematically assessing the interactions among different SDG targets can serve to highlight potential conflicts, tradeoffs and synergies among local programmes and policies, as well as among different interest groups at the local, but also international, levels.…”
Section: ) Trade-offs and Synergiesmentioning
confidence: 99%
“…It adopts what appears as an inclusive discourse and acknowledges that equitable and affordable access to water is a right and need that requires particular attention to the vulnerable, and must be achieved through the elimination of legal, institutional, socio-economic and physical barriers. Caprotti et al (2017) warn against the reductionist approach and numerous assumptions made in the NUA, for example on the states' capacities to deliver on multiple commitments. Satterthwaite (2016) reminds us of the importance of keeping NUA coherent, and more importantly advocates for more power transfer to actors (government and non-government actors) at local level.…”
Section: Synergies In Water Governancementioning
confidence: 99%
“…The sustainable development goals seek to "make cities inclusive, safe, resilient and sustainable" (UN 2016). This statement summarizes and covers most big urban buzzwords of the past two decades, such as climate change and sustainable urban development (Caprotti et al 2017). Sustainable Development Goal 11 is profoundly based on indicators and urban data that are missing in cities of the…”
Section: Discussionmentioning
confidence: 99%